Testing the effectiveness of hair growth tonic with cocoa bean extract on mice for physical stability and activity - Alfian, Muhammad; Hasanudin, Muhammad Nurul; Maulana, Mochamad Luqni (JSFK (Jurnal Sains Farmasi & Klinis), 2023)
Cocoa is a highly valued plant due to its versatile uses, including being processed into cosmetic products. Hair loss and slow hair growth are common hair-related concerns that can be effectively addressed through the use of hair tonics. Previously, research has shown that cocoa bean can effectively stimulate hair growth when made into a cream. Our research aimed to determine the secondary metabolite content of cocoa beans extract, formulate the extract into a hair growth tonic, and test its physical stability and effectiveness on hair growth in mice. Cocoa beans extracted by maceration method and conducted phytochemical screening. This extract was then used to create three formulations with different extract concentrations of 0.2%, 0.3%, and 0.5%, which were tested for physical stability, including organoleptic properties, homogeneity, pH, and specific gravity. Mice were divided into five treatment groups, hair length growth measurements were taken every week, on the 7th, 14th and 21st days. Six strands of hair were taken from the application area, and their length was measured using a calliper. Results revealed that cocoa seed extract contains flavonoids, alkaloids, tannins, and phenolics. The formula with a 0.3% concentration of cocoa bean extract showed the best physical stability. Hair growth tests on mice showed no significant difference between the 0.3% and 0.5% cocoa bean extract formulas and the positive control in the second week. The 0.3% formula is the best for ensuring good physical stability and promoting hair growth in mice when used twice daily for two weeks